EP.WE.213Short-term impact of COVID-19 on surgical services in a tertiary hospital. (28th October 2021) - Hamer, N; Brown, A; Sharma, V; Jha, T; Garg, D; Jha, M
Abstract: Aim: Since December 2019, SARS-CoV-2 has dramatically impacted the global landscape. One of the biggest challenges has been the additional strain put on healthcare systems. Although there are numerous studies on the effects of COVID-19 on intensive care beds and ventilator availability, there has been little exploration into the wider impacts of COVID-19 on the provision of other services. This study was designed to explore how COVID-19 has impacted surgical service provision at a large NHS hospital. Methods: We compared the number and types of general surgical procedures carried out in a tertiary centre in the six months prior to the UK COVID-19 outbreak (September 2019-February 2020) and the six months after (March 2020-August 2020). Results: We found that since March 2020 there has been a 70% decrease in the amount of operations taking place, with numbers dropping from a pre-COVID total of 1761 to a post-COVID total of 529. This mainly affected elective procedures with emergency surgeries remaining relatively constant (48 pre-COVID vs 44 post-COVID). Conclusion: COVID-19 has caused a significant decrease in the number of surgeries being undertaken. This is due to a combination of factors including staffing issues, reduced investigative capacity, and national mandates on the cessation of non-urgent procedures. Although this mainly affected elective operations, it will have wider implications on future NHS workload and training. The knock on effects will inevitably result in a rise in delayed and emergency presentations with worse patient outcomes.